Marketing Management Based on Understanding Car Brand Design - Najihatul Faridy (Journal of Innovative and Creativity, 2025)
The use of language aspects pragmatically is inseparable from its relationship with car product marketing because product design plays a role in the form of communication involving images that determine the level of visual quality of the product for consumers so that they are interested in buying and using it. This study uses a qualitative approach that is presented descriptively to determine the perception and interest of market management based on the design language of car brands such as: Honda, Mitsubishi, Nissan, BMW, and Mazda. Data in this study will be collected by giving tests and open interviews. The data is collected, then the data analysis uses the concept by Miles and Hubermann where the collected data is then presented, reduced, and conclusions are drawn. Design language affects consumer interest in marketing management. The level of understanding of design language is above 50% for each car brand. The constraint in market share is the consumer's economic factor.